Bullying and students with disabilities strategies and techniques to create a safe learning environment for all - McNamara, Barry E. 1949- (Thousand Oaks, California Corwin, a SAGE Company, 2013)
"Drawing on extensive studies on bullying in schools, Barry Edwards McNamara provides a research-based overview to understand bullying. Additionally, this book shows how to identify bullies and victims and implement an effective and inclusive bullying prevention program"-- Back cover.
What is bullying? -- Why are students with disabilities targeted? -- How to identify bullies and their victims -- Creating a school-wide program -- What every teacher must do -- What every paraprofessional should know -- What every parent should know -- Teaching supports and techniques.
Includes bibliographical references (pages 123-130) and index.
Keywords: Bullying; Children with disabilities